2013
DOI: 10.1074/jbc.m112.422048
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Amidation of an Osteocalcin-derived Peptide Promotes Hydroxyapatite Crystallization

Abstract: Background: A natural motif sequence was used as substrate to template hydroxyapatite (HA) formation. Results: HA crystal formation is attributed to C-terminal amidation of a natural peptide derived from osteocalcin. Conclusion: The chemical structure of the peptide controls HA crystal formation and growth. Significance: HA-binding peptides are relevant for biomimetic bone synthesis, hard tissue regeneration, and improvement of osseointegration of biomedical implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…What's more, this synthetic peptide is enriched in proline, in which the carboxal group enhances its interaction with both calcium and phosphate ions, thus effectively promoting hydroapatite crystallization (Hosseini et al, 2013). Secondly, according to the theoretical pI of the peptide, the peptide has negatively charged surfaces in the remineralization solution (pH 7.0), which is believed to interact efficiently with calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…What's more, this synthetic peptide is enriched in proline, in which the carboxal group enhances its interaction with both calcium and phosphate ions, thus effectively promoting hydroapatite crystallization (Hosseini et al, 2013). Secondly, according to the theoretical pI of the peptide, the peptide has negatively charged surfaces in the remineralization solution (pH 7.0), which is believed to interact efficiently with calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the negatively charged ‐COOH in side‐chain of TVH19 was changed to the neutral ‐CONH 2 . Although this change may decrease the growth rate of apatite formation, it was reported to avail to develop c‐axis‐oriented construction, which resembled with the morphology of hydroxyapatite in natural bone tissue (Hosseini et al, ; Li, Lan, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work shows that AMPs do not trigger microbial resistance and some AMPs possess obvious antimicrobial ability against drug‐resistant bacteria, helping to limit microbial resistance resulting from conventional antibiotics (Ma et al, ). As for remineralization, peptides, such as P11‐4, OSN, and 8DSS, have been reported to promote mineral deposition, repair crystalline structures, and reverse the surface characteristics of early caries lesions (Hosseini et al, ; Kirkham et al, ; Yang et al, ). However, so far, no single peptide can simultaneously exert antimicrobial and remineralizing effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, in all of these reports, the needle‐like HA is synthesized at pH ≥ 10, and it is considered that the formation of needle‐like HA is difficult in the neutral oral cavity. However, it has been reported that amino acids constituting proteins control the nucleus formation and crystallization of HA, and by interaction with HA, control the crystal growth in the neutral region (Chang et al, ; Hosseini et al, ; Jahromi et al, ; Larson et al, ; Matsumoto et al, ; Shaw et al, ; Tao et al, ; Zhu et al, ). Accordingly, it is considered that the amino acids in saliva proteins affect the form and structure of HA formed on the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…On the upper side of these needle‐like particles, there were observed whisker‐like HA crystal nanoparticles with a width of several nm and a length of 200 nm, which precipitated and grew in the albumin aqueous solution. It is reported by Hosseini et al () that proteins serve as a template for the nucleus formation and crystallization of HA, and it is considered that the formation of a complex of an acid group of the amino acid in albumin and Ca ion serves as a center for the nucleus formation, and further adsorption of phosphate ion and Ca ion causes formation of a cluster nucleus, whereby whisker‐like HA with a width of several nm is rapidly formed. Thus, it is considered that granular nanoparticles or undefined amorphous substances corresponding to the above A or B were not observed in the model system because of the acceleration of growth period.…”
Section: Discussionmentioning
confidence: 99%